Combined Topography-Guided Trans-Epithelial PRK and PTK for Treatment of Calcific Band Keratopathy Unresponsive to EDTA Chelation Therapy - Passidomo F; Addabbo G; Pignatelli F; Niro A; Buonamassa R (International Medical Case Reports Journal)
Fedele Passidomo,1 Giuseppe Addabbo,1 Francesco Pignatelli,1 Alfredo Niro,1 Rosa Buonamassa2 1Eye Clinic, “SS. Annunziata” Hospital, ASL Taranto, Taranto, Italy; 2Eye Clinic, P.O. “Madonna delle Grazie”, Matera, ItalyCorrespondence: Fedele Passidomo, Eye Clinic, “SS. Annunziata” Hospital, ASL Taranto, Via Francesco Bruno, 1, Taranto, 74121, Italy, Tel +393288569125, Email dotpaoli@yahoo.itPurpose: To report a case of Calcific Band Keratopathy (CBK) treated successfully with transepithelial Phototherapeutic keratectomy (PTK) combined with customized Photorefractive Keratectomy (PRK).Methods: One case report.Results: A 63-year-old man presented to our clinic with decreased visual acuity and ocular discomfort in both eyes. Clinical examination revealed a horizontal gray-whitish band across the central cornea in both eyes, supporting the diagnosis of CBK. Initially, an EDTA chelating procedure was attempted, but it had no effect on the deeper calcium deposits and on the irregular corneal morphology. In both eyes, a topography-guided trans-epithelial PRK with PTK was performed. Following PRK surface ablation, PTK was used to smooth the ablated area using 1% hydroxymethylcellulose as masking agent. The procedure was completed applying 0.02% Mitomycin C. At the 1-month follow-up, both eyes corneal opacities were resolved, and the LE visual acuity had improved to 20/63 and the RE to 20/20, which was maintained at the 3-, 6-, and 12-months follow-up. Furthermore, there was an improvement in spherical equivalent and corneal morphological irregularity index.Conclusion: CBK may be successfully treated using a combined topography-guided trans-epithelial PRK and PTK.Keywords: calcific band keratopathy, corneal degenerations, phototherapeutic keratectomy, topography-guided photorefractive keratectomy